A inquietante estranheza no corpo - Finkelstein, Claudia; Vacheret, Claudine; Hirashima, Cristina Satie; Bombana, José Atílio; Prado, Ricardo Almeida; Volich, Rubens Marcelo (Percurso, 2012)
Realização: Cristiane Abud, Gisela Haddad e Vera Zimmermann